Molecular detection of interleukin-1A +4845 G→T gene in aggresive periodontitis patients - Chiquita Prahasanti; Harianto Notopuro (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: Abundant researches had been conducted based on the clinical and histopathological pathogenesis of aggresive periodontitis. Nevertheless, there were still few researches which based on molecular biology, and especially related to gene polymorphism. This study was done based on IL-1A +4845G→T gene polymorphism in aggressive periodontitis patients. Purpose: The purpose of this tudy was to characterized the generic variation of IL-1A +4845G→T as a risk factor aggressive periodontitis and chronic periodontitis. Methods: DNA from patients with aggressive periodontitis and chronic periodontitis was taken determination of IL-1A +4845 G→T polimorphism was conducted with PCR-RFLP technique. Results: Homozygous allele TT polymorphism was not found in all samples, only allele GG (wild type) and allele GT (heterozygous mutant) were not affect aggressive periodontitis and chronic periodontitis. Conclusion: The study showed there was no significant association between IL-1A +4845G→T gene polymorphism and aggressive periodontitis and chronic periodontitis. Latar belakang: Penelitian tentang patogenesa periodontitis agresif berdasar klinis dan histopatologi telah banyak dilakukan, akan tetapi penelitian berdasar biologimolekuler terutama polimorfisme gen masih sangat jarang dilakukan. Penelitian ini dilakukan berdasarkan pada polimorfisme gen IL-1A +4845G→T pada penderita periodontitis agresif. Tujuan: Tujuan dari penelitian ini adalah untuk mengetahui variasi genetik dari IL-1A +4845G→T yang merupakan faktor risiko periodontitis agresif dan periodontitis kronis. Metode: DNA dari penderita periodontitis agresif dan periodontitis kronis diisolasi, selanjutnya dilakukan determinasi dari polimorfisme gen IL-1A +4845G→T dengan menggunakan teknik PCR-RFLP. Hasil: Pada seluruh sampel penelitian ini tidak dijumpai polimorfisme allel TT (homosigot mutan), yang didapat adalah jenis allel GG (wild type) dan allel GT (heterosigot mutan) yang tidak berpengaruh terhadap periodontitis agresif dan periodontitis kronis. Kesimpulan: Polimorfisme gen IL-1A +4845G→T tidak mempunyai hubungan terhadap kejadian periodontitis agresif dan periodontitis kronis.